2007
DOI: 10.1016/s1808-8694(15)31169-1
|View full text |Cite
|
Sign up to set email alerts
|

Hystology findings' correlation between the ossicular chain in the transoperative and cholesteatomas

Abstract: Our findings indicate that ossicular chain changes are practically universal when a cholesteatoma is present. We didn't find correlations related with bone erosion and cholesteatoma's histological findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 23 publications
1
15
0
1
Order By: Relevance
“…There was no evidence of squamous epithelial cells in the ossicles removed from cholesteatomatous cases. Though ossicular necrosis is more in tubotympanic otitis media, several studies [11,12] show variable percentage. Incidence of ossicular involvement of even up to [90% in atticoantral otitis media has been reported [13].…”
Section: Discussionmentioning
confidence: 99%
“…There was no evidence of squamous epithelial cells in the ossicles removed from cholesteatomatous cases. Though ossicular necrosis is more in tubotympanic otitis media, several studies [11,12] show variable percentage. Incidence of ossicular involvement of even up to [90% in atticoantral otitis media has been reported [13].…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Dornelles et al (16) could not find a correlation between patients' age and perimatrix inflammation intensity or granulation tissue thickness and assessed ossicular damage magnitude. Additionally, In our study, no correlation was found between patients' age and reported duration of the disease and ossicular damage magnitude either.…”
Section: Discussionmentioning
confidence: 78%
“…However, malleus erosion was slightly higher than our study. Dornelles et al [26] (2007), Incus was the most frequently affected and with erosion of long process in 47.6% followed by stapes suprastructure erosion in 32.3% malleus was least eroded.…”
Section: Discussionmentioning
confidence: 96%